Pengaruh Media Wordwall Games terhadap Berpikir Kritis Siswa Kelas IV di SD Saraswati 1: Penelitian - Putu Wahyu Ligyawati, Ni; Dewi Pusparini, Luh; Ketut Manik Asta Jaya, I (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This scientific exploration is intended to identify the implications of the use of the Open the Box type Wordwall Games on the critical reasoning capacity of grade IV students in the Pancasila Education subject group, especially in the discussion of "Efforts to Appreciate the Diversity of Nusantara Culture." This study adopts a numerical approach with a quasi-experimental method and a Pretest-Posttest Control Group Design. The subjects in this study were divided into two groups, namely the treatment group (29 students) and the comparison group (29 students). The data acquisition procedure was carried out through critical reasoning testing in the form of multiple-choice questions that had previously gone through a validity and reliability verification process. The information obtained was analyzed using the t-test and N-Gain calculations, using the 29th edition of SPSS statistical software. The research findings indicate a significant correlation between the implementation of the Wordwall Games Open the Box instrument and the improvement of students' critical thinking skills. The experimental group showed an average pre-test score of 72.17 and a post-test score of 92.93 with an N-Gain achievement of 0.7590 (classified as high), while the control group recorded a pre-test score of 66.52 and a post-test score of 79.66 with an N-Gain of 0.3866 (medium category). The significance results of the t-test showed a Sig. (2-tailed) value <0.001.